Data charges, delivery dependability, geographical distance, product risk and information quallity as predictors of online purchase intention in the South African retail sector - Luthuli, Menelisi Minenhle (My University, 2017)
The continuous growth of e-commerce has led to a keen interest in the uptake of online shopping. This phenomenon is even more prevalent in developed western countries. However, penetration has taken place at a lessor rate in developing countries in most parts of Africa including South Africa. Apart from infrastructural capability and adequate online store reputation, the success of online shopping fundamentally rests upon e-tailers who are able to capture consumers by understanding what variables drive them to shop online. Although several studies have explored factors that drive online purchase intention, few have explored variables of interest as done in this present study. More specifically, this sort of research is scarce within the South African general merchandise online retail sector. This study aims to determine whether data charges, delivery dependability, geographical distance, product risk and information quality have any influence on consumers‘ online purchase intention. The conceptual model adopted in this study selected data charges, delivery dependability, geographical distance, product risk and information quality as predictor variables, online shopping satisfaction and trust as mediating variables and online purchase intention as the outcome variable. This is a quantitative study whereby 20 000 online survey questionnaires were distributed to a base of two renowned South African online retailers who predominately specialize in general merchandise. Of those distributed, 924 were complete and thus deemed useable by the researcher. The findings support all eight proposed hypotheses, therefore indicating that the aforementioned variables indeed influence online purchase intention at varying levels of significance. The study seeks to contribute new contextual knowledge, adding to the existing literature linked to online retailing and to contribute new empirical and theoretical findings. The research findings highlight new insights to marketing practitioners who, with better understanding of consumer decision making theory, will be able to create strategies that can be employed to influence consumers‘ online purchase intention in the South African general merchandise online retail sector. Keywords: E-commerce, online shopping, purchase intention, general merchandise retail.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy, School of Economic and Business Sciences, 2017
Keywords: Teleshopping--South Africa; Internet marketing--South Africa; Electronic commerce--South Africa; Consumer behavior--South Africa